Operando Analysis of Electron Accumulation in Titanium(IV) Oxide Particles in an Aqueous Suspension Using a Photoacoustic Spectroscopic Method - Murakami, Naoya; Shinoda, Tatsuki (Journal of physical chemistry. C, 2019)
The time course of photoabsorption of an aqueous suspension of titanium(IV) oxide (TiO2) particles was studied using photoacoustic (PA) spectroscopy. In the absence of an electron acceptor and the presence of an electron donor, ultraviolet irradiation increased PA intensity because photoabsorption of the suspension increased due to trivalent titanium (Ti3+) species generated by electron accumulation in TiO2 particles. In contrast, the addition of methylene blue (MB) as an acceptor caused a decrease in PA intensity, indicating that accumulated electrons were consumed by reduction of MB to colorless leuco-MB. The results for various TiO2 particles indicated that Ti3+ density is determined by this method. Moreover, the measurement can be applicable to quantitative operando analysis for accumulated electrons in a photocatalytic reaction.